2021
DOI: 10.3389/fnut.2021.732237
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Legume Purchases and Consumption in the United States

Abstract: Background: Legumes are an inexpensive, healthy source of protein, fiber, and micronutrients, have low greenhouse gas and water footprints, and enrich soil through nitrogen fixation. Although higher legume consumption is recommended under US dietary guidelines, legumes currently comprise only a minor part of the US diet.Objectives: To characterize the types of legumes most commonly purchased by US consumers and patterns of legume purchases by state and region, seasonality of legume purchases, and to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Shifting dietary patterns toward higher legume, nut, and seed consumption requires significant changes in behavior, knowledge, and food preparation skills. A question therefore remains on how feasible such shifts would be given current dietary practices (Semba et al, 2021b).…”
Section: The Trend In Overlooking and Oversimplifying The Importance ...mentioning
confidence: 99%
“…Shifting dietary patterns toward higher legume, nut, and seed consumption requires significant changes in behavior, knowledge, and food preparation skills. A question therefore remains on how feasible such shifts would be given current dietary practices (Semba et al, 2021b).…”
Section: The Trend In Overlooking and Oversimplifying The Importance ...mentioning
confidence: 99%
“…Legumes (common beans, chickpeas, lentils, broad beans, etc.) are very complete foods because they contain almost all the nutrients we need; however, their consumption has drastically decreased (21 g/person/day), maybe due to their loss of prestige in developed countries [ 67 ]. Legumes are an important source of protein, dietary fiber, complex carbohydrates, iron, zinc, B complex vitamins and essential amino acids and are practically free of saturated fats [ 68 , 69 ].…”
Section: Macro- and Micro-nutrients In Foodsmentioning
confidence: 99%
“…Despite the many disease-prevention and health-enhancing qualities associated with legume intake, consumption levels tend to be modest in the U.S. and appear to be decreasing [ 7 , 8 ]. Based on purchasing data from grocery stores, chain supermarkets, club stores, and other retail outlets, Semba et al concluded in 2021, “Although legumes are inexpensive, healthy, and a sustainable source of protein, per capita legume intake remains low in the U.S. and below dietary guidelines” [ 9 ].…”
Section: Introductionmentioning
confidence: 99%